2010
DOI: 10.1109/tits.2010.2055239
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern-Recognition Approach for Driving Skill Characterization

Abstract: Information about a driver's driving skill can be used to adapt vehicle control parameters to facilitate the specific driver's needs in terms of vehicle performance and safety. This paper presents an approach to driving skill characterization from a pattern-recognition perspective. The basic idea is to extract patterns that reflect the driver's driving skill level from the measurements of the driver's behavior and the vehicle response. The experimental results demonstrate the feasibility of using a pattern-rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Our driving behavior characterization algorithms are based on a pattern-recognition approach. Although the modeling relies on an idea proposed by Zhang [77], the difference between the proposals is the fact that Zhang's work aims to identify the driver's skill level (e.g., expert or novice) through receiving driver behavior measurements as input. Our research aims to identify driver behavior based on online outlier detection through measurements of the signals from different sensors embedded onboard the vehicle, as well as sensors of the mobile device onboard the vehicle.…”
Section: Online Cep-based Outlier Detection Algorithmsmentioning
confidence: 99%
“…Our driving behavior characterization algorithms are based on a pattern-recognition approach. Although the modeling relies on an idea proposed by Zhang [77], the difference between the proposals is the fact that Zhang's work aims to identify the driver's skill level (e.g., expert or novice) through receiving driver behavior measurements as input. Our research aims to identify driver behavior based on online outlier detection through measurements of the signals from different sensors embedded onboard the vehicle, as well as sensors of the mobile device onboard the vehicle.…”
Section: Online Cep-based Outlier Detection Algorithmsmentioning
confidence: 99%
“…A wide variety of research on driver modeling has been reported [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, very few studies have been explicitly characterized driving skill in terms of driving action [14][15][16][17][18][19][20] and applied this using machine learning methods.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, when a driver is performing additional tasks unrelated to driving and is under higher workload, changes can be observed in features of the steering wheel angle (SWA) (Mehler et al, 2012). To determine the skill level of drivers, Zhang et al (2010) use vehicle simulator telemetry data from typical and expert drivers as they performed several manoeuvres. As typical drivers were more numerous than experts, the data was re-sampled so that it included the same number of typical drivers as experts, although under-sampling of manoeuvres from all drivers may have been more appropriate.…”
Section: Related Workmentioning
confidence: 99%